KERJASAMA DALAM PENGADAAN SARANA & PRASARANA PADA SEKOLAH DASAR NEGERI 23 TRANSMIGRASI III DESA TUNGGAL BHAKTI KECAMATAN KEMBAYAN KABUPATEN SANGGAU - Endang Apriani E.01110098 (FISIP Universitas Tanjungpura, 2014)
Problems on facilities and infeastructures at Primary School No 23 occured because there had not good cooperation in the provition of facilities and infrastructures at Primary School No 23 Transmigrasi III. The purpose of this research was to describe and analyze the cooperation in the provision of facilities and infrastructures at Primary School No 23 Transmigrasi III. The cooperation specifically focused on internal cooperation in the school. The cooperation included budget analysis, analysis of financing, selection, acquisition and financing, and managemen of provision of facilities and infrastruktures covering planning, organizing, movemen and supervising therefore the school facilities and infrastructures can be accomplised. The research used explorative- qualitative research. The researchfindings showed that the problems on facilities and infrasuctures at primary school No 23 occured because there has not good cooperation in the provision of fasilities and infrastructures at Primary School No 23 Transmigrasi III caused by several factors such as complex system, limited budget, long realization and poor management. Based on the problem above, it was suggest that the school could have good cooperation both internal and external and improved its provision managemen. Keywords: facilities and Infrastructures, Innovation, Cooperation, Management and Primary School